2016
DOI: 10.1089/neu.2014.3831
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Regional Brain Volumes Two Months and One Year after Mild Traumatic Brain Injury

Abstract: Conventional structural imaging is often normal after mild traumatic brain injury (mTBI). There is a need for structural neuroimaging biomarkers that facilitate detection of milder injuries, allow recovery trajectory monitoring, and identify those at risk for poor functional outcome and disability. We present a novel approach to quantifying volumes of candidate brain regions at risk for injury. Compared to controls, patients with mTBI had significantly smaller volumes in several regions including the caudate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 18 publications
7
30
1
Order By: Relevance
“…This is in line with Zagorchev who observed reductions in subcortical structures, including the caudate nucleus [26]. Mounting evidence indicates that the caudate nucleus plays an important role in processing information and relays this information back to distinct cortical regions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is in line with Zagorchev who observed reductions in subcortical structures, including the caudate nucleus [26]. Mounting evidence indicates that the caudate nucleus plays an important role in processing information and relays this information back to distinct cortical regions.…”
Section: Discussionsupporting
confidence: 89%
“…Some longitudinal studies have described the development of atrophy after MTBI [23][24][25][26][27][28]. In contrast, two other studies observed no atrophy in patients diagnosed with MTBI [16,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 The thalamus functions as a sensory relay center with projections to multiple cortical regions. 10 Prior studies show the thalamus is susceptible to injury and can result in decreased volume, 11, 12 inflammation, 13 and reduced perfusion. 14 Early magnetic resonance imaging (MRI) studies using fractional anisotropy found associations between the thalamus and TBI symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Two clinical data sets were used for validation: (1) a 2D set of 100 femur boundaries segmented automatically using a clinically employed software (Hologic Apex 3.2) from dual-energy X-ray absorptiometry images of healthy subjects; (2) a 3D set of 30 caudate nuclei, segmented automatically [10] from T1-weighted MR images 1 of healthy subjects. Point sets were generated from these segmentations using a marching cubes-based surface extraction algorithm.…”
Section: Resultsmentioning
confidence: 99%